ИСПОЛЬЗОВАНИЕ МЕТОДА МОЗГОВОГО ШТУРМА ПРИ ИЗУЧЕНИИ ТЕМЫ АЛЬТЕРНАТИВНЫХ ИСТОЧНИКОВ ЭНЕРГИИ В АКАДЕМИЧЕСКОМ ЛИЦЕЕ - Камалов, А.Б.; Турсынбаев, С.А. (SCIENCE and SOCIETY, 2025)
The article analyzes the use of brainstorming in studying the topic “Alternative Energy Sources” at an academic lyceum. It highlights the importance of developing creative thinking, teamwork, and the ability to generate innovative solutions. Using a lesson on improving solar panel efficiency as an example, the stages and practical significance of the method are demonstrated.